The Nomenclature of Human White Matter Association Pathways: Proposal for a Systematic Taxonomic Anatomical Classification - Mandonnet, Emmanuel; Sarubbo, Silvio; Petit, Laurent (Frontiers in Neuroanatomy, 2018)
The heterogeneity and complexity of the white matter (WM) pathways of the human brain were discretely described by pioneers such as Willis, Stenon, Malpighi, Vieussens, Vicq d’Azyr and others up to the beginning of the XIXth century. Therefore, novel approaches to gross dissection of brain internal structures led to a new understanding of the WM organization, notably thanks to the works of Reil, Gall and Burdach highlighting its fascicular organization. Meynert then proposed a definitive tripartite organization in association, commissural and projection WM pathways. The enduring anatomical work of Dejerine in the turn of the XXth century describing the WM pathways in detail has been the paramount authority on this topic, including their terminology, for over a century, enriched sporadically by studies based on blunt Klingler dissection. Nowadays, diffusion-weighted magnetic resonance imaging (DWI) is used to reveal in vivo the WM fiber tracts of the human brain by measuring the diffusion of water molecules, especially along axons. It is then possible by tractography to reconstitute step by step the WM pathways at an unprecedented level of precision in large cohorts of human brain. However, as powerful they may be, tractography algorithms still face the complexity of the organization of WM pathways and there is a crucial need to benefit from exact definitions of the trajectories and endings of all WM fascicles. Beyond such definitions, the emergence of DWI-based tractography mostly revealed a strong heterogeneity in naming the different bundles, especially the long-range association pathways. This review deals with the various terminologies known for the WM association bundle, aiming to describe the rules of arrangements followed by these bundles and to propose a new nomenclature based on the structural wiring diagram of the human brain.